Photomask Technology 2018 2018
DOI: 10.1117/12.2502480
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of the impact of EUV pellicles on reticle imaging

Abstract: The purpose of EUV pellicles is to protect the surface of EUV lithography masks from particle contamination. Currently several pellicle prototypes are being developed. It is important to ensure that the optical characteristics of the pellicle membrane do not critically affect the reticle image quality. We present here a study of the impact of a few selected EUV pellicle prototypes on the quality and the contrast of the reticle image obtained with an actinic lensless microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Also, it is suspected that random scattering by the contaminant and pellicle could have resulted in blurry lines at the edge of the image. 27 The existence of contaminants is evident when we observe the EUV intensity profile across the L/S patterns. While the EUV intensity profile of the naked EUV mask [Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Also, it is suspected that random scattering by the contaminant and pellicle could have resulted in blurry lines at the edge of the image. 27 The existence of contaminants is evident when we observe the EUV intensity profile across the L/S patterns. While the EUV intensity profile of the naked EUV mask [Fig.…”
Section: Resultsmentioning
confidence: 82%
“…We have demonstrated that RESCAN is capable of detecting programmed defects on EUV logic patterns using die-to-die and die-to-database approaches, 3 and we tested it on pellicle-covered samples, evaluating the impact of different types of pellicles on the image quality. 9 We describe here the experiments performed in order to evaluate the inspection sensitivity of RESCAN for absorber and phase defects.…”
Section: Rescan Working Principle and Layoutmentioning
confidence: 99%
“…We have demonstrated that RESCAN is capable to detect programmed defects on EUV logic patterns using die-to-die and die-to-database approaches 2 and we tested it on pellicle-covered samples, evaluating the impact of different types of pellicles on the image quality. 8 We describe here the experiments performed in order to evaluate the inspection sensitivity of RESCAN for absorber and phase defects.…”
Section: Rescan Working Principle and Layoutmentioning
confidence: 99%
“…The RESCAN actinic pattern inspection microscope is a research and development platform for EUV mask inspection based on lensless imaging. After demonstrating the feasibility of actinic pattern inspection in dieto-die and in die-to-database mode, 2 and the ability of the microscope to inspect samples equipped with EUV pellicles, 8 we wanted to test the current defect sensitivity of RESCAN for absorber and buried structures. To investigate RESCAN's sensitivity to absorber defects, we fabricated a sample consisting of a multilayer-coated silicon wafer and a 140-nm thick HSQ absorber layer.…”
Section: Conclusion and Future Plansmentioning
confidence: 99%